Numerical analysis of detonation stability in a rotating detonation engine fuelled with biogas and hydrogen - Rahman, Mohammad Nurizat (2022)
The novel rotating detonation engine (RDE) fuelled with biogas offers a significant contribution to the application o f combustion engines powered by renewable-based fuels. However, the potential of a biogas-fuelled RDE has never been properly examined in terms o f key operating parameters such as ignition intensity, equivalence ratio, and total mass flow rate (MFR). Hence, the primary research goal for the current numerical study was to examine the stability o f continuous rotating detonation waves (CRDW) in RDEs powered by hydrogen and biogas on the basis of the aforementioned operating parameters. The numerical model o f CRDW was first established to represent the CRDW stability. Following that, the modified one-step chemistry for biogas detonation was developed and merged with the validated CRDW numerical model. The impact o f the above-mentioned critical operating parameters on CRDW stability in the biogas-fuelled RDE was explored using the validated CRDW numerical model, which was merged with the modified one-step chemistry for biogas detonation. The CRDW numerical model revealed that the predicted CRDW pressure was within 10% of the experimental data. The one-step model was compared to experimental data and the detailed chemistry data, revealing 15.75% and 8.29% discrepancies in biogas detonation velocities. The result is that in a fuel-lean nonpremixed environment at fixed ignition intensities, the biogas-fuelled RDE outperformed the hydrogen counterpart in terms o f detonation stability, with the predicted time to achieve a stable one-wave CRDW in the former RDE being 1327 microseconds shorter than that of the latter RDE. However, the former RDE fell short in detonation sustainability, as predicted by the wave longevity. After 0.0146 seconds from the one-wave emergence, the CRDW was extinguished in the former RDE, while the CRDW pressure was only decreased by 1.52% in the latter RDE. The fundamental explanation for this was that biogas, which has lower diffusivity and reactivity than hydrogen, created an imbalance in counter-rotating waves, resulting in a faster CRDW mode transition than hydrogen. Multiple collisions o f counter-rotating waves have been discovered to be the primary mechanism in the CRDW stabilization process. There was a balance between gaining and losing energy for counter-rotating waves, culminating in a CRDW mode transition or CRDW extinguishment. The enhanced ignition intensity, equivalence ratio, and MFR produced the expected increase in CRDW intensity in the biogas-fuelled RDE. Enhancing these parameters aided in boosting the detonability of the biogas-air mixture. Quasi one-wave CRDW was observed from the start of ignition in all parametric cases, showing that the state of chaotic detonation instability was hardly occurred using biogas. To conclude, the current study discovered that the CRDW from the biogas-fuelled RDE has a more comprehensive operating stability range than the hydrogen-fuelled counterpart. Still, the rapid biogas detonation decay highlights the necessity for an enhanced mixing rate to preserve detonation continuity. The assessment of CRDW instabilities in the current study is pivotal for ensuring that these instabilities are effectively regulated and taken into account during the establishment o f a RDE powered by biogas. The findings will also spearhead further research into parameters that could sustain CRDWs in the future working prototype o f biogas-fuelled RDE.